Bagaimana Product Knowledge dan Product Involvement Memotivasi Konsumen? (Kajian Motivasi Masyarakat Terhadap Pemilihan Jurusan Komunikasi Pemasaran Universitas Bina Nusantara sebagai Tempat Melanjutkan Pendidikan Tinggi) - Damanik, Elsye Rumondang (Bina Nusantara University, 2013)
Consumers require knowledge and involvement upon consuming products/services. In order to find out the characteristics of the products/services, consumers perform certain efforts from searching information through the media, being directly involved by using the products/services, to asking questions to the products/services users. Consumers? level of interest and ability in deciding which products/services they want to use also vary. Consumers are highly influenced by product knowledge, and (personal) involvement with the chosen products/services. This research aims at understanding how characteristics of products/services and personal involvement motivate consumers in using the services of Jurusan Komunikasi Pemasaran Universitas Bina Nusantara. Using quantitative research approach, this research tried to understand the level of validity and reliability of research instrument, the efficiency of research instrument, and relationship among variables. The result showed that the research instrument is valid and reliabel. The reliability is stated from the Cronbach Alpha value of each variable (product knowledge = 0,877; product involvement = 0,734; motivation = 0,836). The instrument is valid with Corrected Item-Total Correlation value of 0,148 (approx. df = N-2; or df = 164). It is concluded that consumers? product knowledge and product involvement to Jurusan Komunikasi Pemasaran Universitas Bina Nusantara motivate the (future) students in putting it as the preferred place to have quality education. One of the suggestions is to invite more media practitioners during Open House Program since it will enable the (future) students to have better understanding on the communication related activities.